Immunomodulatory Effects of MANGIFERA INDICA on Haematological Parameters and Kidney Architecture of Breast Cancer-Induced Albino Rats. - Alhassan Hussaini Mohammed,Usman Malami Aliyu, Isiyaku Adamu, Samuel Bamaiyi Dadzie, Abdulrahman Abdullatif, Abdullahi. Mainasara, Yakubu Abdulrahman, and Hamisu Abdullahi (Sokoto Journal of Medical Laboratory Science)
Breast cancer is one of the most common cancers found in women worldwide, accounting for more than half a million deaths in 2015. Over 1.5 million women are diagnosed with breast cancer every year throughout the world. Breast cancer is a metastatic cancer which is commonly transferred to distant organs such as the bone, liver, lung and brain. Biological therapies have been developed in recent years but despite that, a lot needs to be done in addressing the treatment for these strata of patients. The present study investigated the effects of Mangifera indica in the modulation of haematological indices in breast cancer-induced albino rats. Twenty-four female albino rats were used for the study, and they were grouped into six groups of four albino rats each. Group 1 (normal control) was fed with normal growers feed. Group 2-6 were orally administered 65 mg/kg body weight of DMBA to induce tumour. Group 2 was untreated; Group 3 was treated with a daily intraperitoneal injection of ascorbic acid [12 mg/kg/day] for 2 weeks. Groups 4- 6 were treated with 500,1000 and 1500 mg/kg body weight of M. indica stem bark extract. The animals were sacrificed 24hrs after the last treatment. The present study reveals that the plant extract was able to reduce anaemia and inflammation posed as a result of breast cancer. WBC, Lymphocyte, RBC and PCV were significantly upregulated in the group treated across most of the group treated with the various doses of M. indica. M. indica may possess immunosuppressive and immunomodulatory potentials and may be of benefit in the management of breast cancer.